Developing TPS- and PAKEM-Based Teaching Materials for Junior High School Students' Fairy Tale Listening Skills - Nursaid Nursaid; Ridha Hasnul Ulya (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study aims to develop and evaluate teaching materials for listening skills in fairy tale texts that integrate the Think-Pair-Share (TPS) model and the PAKEM (Active, Creative, Effective, and Enjoyable Learning) approach to bridge the pedagogical gap in junior high schools. The research method uses an ADDIE-based research and development (R&D) model, involving 128 students and 12 Indonesian language teachers in Padang City as participants. Data were collected through test instruments, observations, and expert validation, then analyzed using a mixed-methods design with concurrent triangulation. The results show that the developed materials have very high validity (M > 97%), reliable instruments, and context-specific effectiveness (tcalc = 4.70 > tcrit = 1.70). The practicality of the materials also reached a high level with a PAKEM score of 84.36%, although the active learning aspect still requires optimization. It is concluded that the holistic synthesis of TPS and PAKEM produces a valid, effective, and practical listening instructional product in the tested classroom context. The implications of this research emphasize the urgency of providing "ready-to-use" materials as a pedagogical bridge for teachers, as well as the need for ongoing scaffolding to transform listening from a passive activity into an enjoyable, student-centered, socio-cognitive event.